Features of atherosclerosis in carotid and coronary arteries - E. V. Konstantinova; A. A. Bogdanova; A. A. Sagatelyan; A. I. Kovaikin; E. S. Pershina; M. Yu. Gilyarov (Медицинский совет, 2021)
Atherothrombosis is a leading cause of myocardial infarction and ischemic atherothrombotic stroke. It represents a stage of atherosclerosis which is a pathologic process throughout the circulatory system. However, atherosclerosis has specific development characteristics in  different vascular beds. Multiple factors contribute to atherosclerosis formation and progression such as genetic factors, vessel hemodynamics, and vessel anatomy. A better understanding of differences in vessels would improve prevention and treatment of atherosclerosis and its complication. In this article we review features of atherosclerosis in carotid and coronary vessels. We discuss specific conditions of local hemodynamics in the areas of bifurcation which promote atherosclerotic plaque progression, and review characteristics of unstable plaques in carotid and coronary vessels. We analyze immunologic and inflammatory processes, extracellular matrix degradation and remodeling, cellular apoptosis and autophagy occurring during atherosclerotic plaque destabilization as well as the possibility of diffuse plaque instability in systemic atherosclerosis. We review association and interaction of  atherosclerotic processes in  coronary and carotid arteries, and its significance for a patient. Improvement in understanding of atherosclerosis pathogenesis can lead to advances in atherosclerosis prevention. Timely and effective interventions would promote prevention of myocardial infarction and ischemic stroke which is highly important taking into account high mortality and morbidity rates.